Analysis of the spatial and transmural dispersion of repolarization and late potentials derived using signal‐averaged vector‐projected 187‐channel high‐resolution electrocardiogram in patients with early repolarization pattern. Issue 6 (24th February 2014) - Ohkubo, Kimie; Watanabe, Ichiro; Okumura, Yasuo; Sonoda, Kazumasa; Sasaki, Naoko; Kogawa, Rikitake; Takahashi, Keiko; Nakai, Toshiko; Kunimoto, Satoshi; Kasamaki, Yuji; Hirayama, Atsushi
Abstract: Background: Electrophysiological characteristics of early repolarization syndrome (ERS), i.e., the spatial and transmural dispersion of ventricular repolarization and ventricular late potentials can be evaluated using a signal‐averaged vector‐projected 187‐channel high‐resolution electrocardiogram (187‐ch SAVP‐ECG). We investigated these characteristics as markers of ventricular fibrillation and sudden cardiac arrest in patients presenting with an ER pattern. Methods: The 187‐ch SAVP‐ECGs were recorded for 8 patients with idiopathic ventricular fibrillation associated with ERS (ERS patients), and 5 patients with an ER pattern without arrhythmic events (ER pattern patients). Results: The ER pattern was located in the inferior leads ( n =7), lateral leads ( n =1), or both inferior and lateral leads ( n =5). The corrected RT(RTc ) (peak point of the R wave − positive maximum peak of the first derivative of the T wave interval corrected using the Bazett formula) interval and T (peak‐end)‐c interval from the 187 channels were calculated. Late potentials were positive in 7 of 8 ERS patients and in 3 of 5ER pattern patients ( P =0.25). The average RTc was shorter in patients with ERS (192.6±29.8 ms vs. 234.0±25.5 ms, P =0.04). However, average T (peak‐end)‐c interval did not differ between the 2 groups. Conclusion: Late ventricular potentials were common in ERS and ER pattern patients. Lethal arrhythmia in ERS patients appeared to be related to the relatively short average repolarization time rather than the spatial and transmural dispersion of repolarization.